Assessing predictors of respiratory tract infections in infants born to teenage mothers: secondary analysis of the Building Blocks trial data. (22nd April 2020) - Buchanan, Emily; Cannings-John, Rebecca; Lugg-Widger, Fiona; Hood, Kerry; Butler, Christopher; Robling, Mike
Abstract: Background: Respiratory tract infections (RTIs) are estimated to account for 60% of infants' primary care visits. There is limited research into risk factors for infant RTIs in those born to teenage mothers. Aims: To identify risk factors for primary and secondary care RTI attendances, in infants of teenage mothers, and to identify risk factors associated with high primary care RTI consultations. Method: Secondary analysis of a data set from the Building Blocks trial of special home visiting support in England containing 1510 infants born to teenage mothers recruited to the study. Maternally reported and routinely collected data were examined. Multivariable logistic regression models were performed to determine independent predictors. Primary care data analysis also focused on infant risk factors for RTI consultation. Results: No independently predictive risk factors for infant RTI were identified in primary care. Lower maternal antenatal attendances (odds ratio = 0.96, 95% confidence interval = 0.92–0.99), infants born in autumn (vs. spring; 0.54, 0.36–0.80) and neonatal unit (NNU) admissions (0.51, 0.30–0.89) had increased odds of attending accidents and emergencies with an RTI. Male infants (1.52, 1.03–2.25), NNU admissions (3.21, 1.98–5.22) and birth season had increased odds of RTI-associated hospital admissions. High infant RTI primary care consulters were more likely to have an RTI-associated hospital admission (2.11, 1.17–3.81) and less likely to have breastfed (0.55, 0.38–0.78). Conclusion: Risk factors previously found to increase the risk of an RTI infant admission in the broader population have been identified here. This study is one of the first to identify modifiable risk factors of high primary care RTI consulters.